Antischistosomal, antionchocercal and antitrypanosomal potentials of some Ghanaian traditional medicines and their constituents - Osei-Safo, D.; Twumasi, E.B.; Akazue, P.I. (PLOS, 2020)
Background Ghana is endemic for some neglected tropical diseases (NTDs) including schistosomiasis, onchocerciasis and lymphatic filariasis. The major intervention for these diseases is mass drug administration of a few repeatedly recycled drugs which is a cause for major concern due to reduced efficacy of the drugs and the emergence of drug resistance. Evidently, new treatments are needed urgently. Medicinal plants, on the other hand, have a reputable his- tory as important sources of potent therapeutic agents in the treatment of various diseases among African populations, Ghana inclusively, and provide very useful starting points for the discovery of much-needed new or alternative drugs. Methodology/Principal findings In this study, extracts of fifteen traditional medicines used for treating various NTDs in local communities were screened in vitro for efficacy against schistosomiasis, onchocerciasis and African trypanosomiasis. Two extracts, NTD-B4-DCM and NTD-B7-DCM, prepared from traditional medicines used to treat schistosomiasis, displayed the highest activity (IC50 = 30.5 μg/mL and 30.8 μg/mL, respectively) against Schistosoma mansoni adult worms. NTD-B2-DCM, also obtained from an antischistosomal remedy, was the most active against female and male adult Onchocera ochengi worms (IC50 = 76.2 μg/mL and 76.7 μg/mL, respectively). Antitrypanosomal assay of the extracts against Trypanosoma brucei brucei gave the most promising results (IC50 = 5.63 μg/mL to 18.71 μg/mL). Incidentally, NTD-B4- DCM and NTD-B2-DCM, also exhibited the greatest antitrypanosomal activities (IC50 = PLOS NEGLECTED TROPICAL DISEASES PLOS Neglected Tropical Diseases | https://doi.org/10.1371/journal.pntd.0008919 December 31, 2020 1 / 21 a1111111111 a1111111111 a1111111111 a1111111111 a1111111111 OPEN ACCESS Citation: Twumasi EB, Akazue PI, Kyeremeh K, Gwira TM, Keiser J, Cho-Ngwa F, et al. (2020) Antischistosomal, antionchocercal and antitrypanosomal potentials of some Ghanaian traditional medicines and their constituents. PLoS Negl Trop Dis 14(12): e0008919. https://doi.org/ 10.1371/journal.pntd.0008919 Editor: Sabine Specht, University of Zurich, SWITZERLAND Received: April 20, 2020 Accepted: October 26, 2020 Published: December 31, 2020 Peer Review History: PLOS recognizes the benefits of transparency in the peer review process; therefore, we enable the publication of all of the content of peer review and author responses alongside final, published articles. The editorial history of this article is available here: https://doi.org/10.1371/journal.pntd.0008919 Copyright: © 2020 Twumasi et al. This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited. Data Availability Statement: All relevant data are within the manuscript and its Supporting Information files. 5.63 μg/mL and 7.12 μg/mL, respectively). Following the favourable outcome of the antitry- panosomal screening, this assay was selected for bioactivity-guided fractionation. NTD-B4- DCM, the most active extract, was fractionated and subsequent isolation of bioactive con- stituents led to an eupatoriochromene-rich oil (42.6%) which was 1.3-fold (IC50 <0.0977 μg/ mL) more active than the standard antitrypanosomal drug, diminazene aceturate (IC50 = 0.13 μg/mL). Conclusion/Significance These findings justify the use of traditional medicines and demonstrate their prospects towards NTDs drug discovery.
Research Article
Keywords: Ghana; Neglected tropical diseases; Traditional medicines; Vitro